2011
DOI: 10.1007/s11356-011-0588-z
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity associated with oxidative damage in the liver and kidney of mice exposed to dimethoate subchronic intoxication

Abstract: Our study demonstrated that DM induced DNA damage in the liver and kidney of treated mice in a dose-dependent manner; this induction was associated to DM-induced oxidative stress. Further investigations are needed to prove the implication of oxidative stress in genotoxicity induced by DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 65 publications
0
8
1
Order By: Relevance
“…Rattner and Hoffman (1984) report the inhibition of AChE after the administration of sublethal oral doses of the organophosphate (OF) insecticide acephate to wild mice (M. musculus, P. leucopus and M. pennsylvanicus); inhibition rates were similar to those reported in this study (16 to 40 %) at doses between 25 mg/kg and 100 mg/kg of food for 5 days. In addition, the inhibition rates recorded in our results are seemingly harmless for the mouse populations, as in other U/min/mg prot ever, the average values recorded in this work are higher than those reported in other (experimental) studies, where mean activity ranges from 0.2 to 2.5 U/min/mg protein (Ayed-Boussema et al 2012;Panemangalore and Baby 2000;Yilmaz et al 2004). In this regard, catalase is a biomarker that can react in different ways, i. e., inhibition or activation, depending on various factors, mainly the dose of the xenobiotic, time of exposure, or a combination of various compounds (van der Oost et al 2003).…”
Section: Resultscontrasting
confidence: 66%
“…Rattner and Hoffman (1984) report the inhibition of AChE after the administration of sublethal oral doses of the organophosphate (OF) insecticide acephate to wild mice (M. musculus, P. leucopus and M. pennsylvanicus); inhibition rates were similar to those reported in this study (16 to 40 %) at doses between 25 mg/kg and 100 mg/kg of food for 5 days. In addition, the inhibition rates recorded in our results are seemingly harmless for the mouse populations, as in other U/min/mg prot ever, the average values recorded in this work are higher than those reported in other (experimental) studies, where mean activity ranges from 0.2 to 2.5 U/min/mg protein (Ayed-Boussema et al 2012;Panemangalore and Baby 2000;Yilmaz et al 2004). In this regard, catalase is a biomarker that can react in different ways, i. e., inhibition or activation, depending on various factors, mainly the dose of the xenobiotic, time of exposure, or a combination of various compounds (van der Oost et al 2003).…”
Section: Resultscontrasting
confidence: 66%
“…Extensive data suggest that free radical formation and oxidative stress can be a major contributor to the toxicity of pesticides (108)(109)(110)(111)(112)(113). OPs are oxidants and impair enzymatic antioxidant defences, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione S-transferase (GST) (23,34,44,(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129). Malathion, methyl parathion, and parathion in HepG2 cell lines, as well as chlorpyrifos, methidathion, chlorfenvinphos, and dimethoate in rat liver and diazinon in fish most probably disrupt membrane lipids through oxidative stress (23,35,61,116,118,(130)(131)(132)(133)(134)(135).…”
Section: Possible Effects Of Ops On Hepatic Oxidative Stress Pathwaysmentioning
confidence: 99%
“…Several in vivo and in vitro studies reported that the genotoxicity of OPs such as dimethoate, methyl parathion, chlorpyrifos, phorate, and malathion in hepatocytes was associated with oxidative damage (130,131,127,(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159). A study by Hreljac et al (160) showed that methyl paraoxon was less genotoxic in HepG2 cells than its parent OP methyl parathion.…”
Section: Possible Mutagenic Genotoxic and Carcinogenic Effects Of Opsmentioning
confidence: 99%
“…Dimethoate (DM), one of the most popular organophosphorus insecticides, is frequently used against a wide range of insects in agriculture and for housefly control due to its high effectiveness (Priya et al, ; Ayed‐Boussema et al, ; Guo et al, ). The residue of DM and its analog have been found in soil, crops, water, and foods, including cow's milk (Amara et al, ; Soler et al, ; Feng et al, ).…”
Section: Introductionmentioning
confidence: 99%